A review of skeletal dysplasia research in India - A Uttarilli (Journal of Postgraduate Medicine, 2018)
We aimed to review the contributions by Indian researchers to the subspecialty of skeletal dysplasias (SDs). Literature search using specific keywords in PubMed was performed to retrieve all the published literature on SDs as on July 6, 2017. All published literature on SDs wherein at least one author was from an Indian institute was included. Publications were grouped into different categories based on the major emphasis of the research paper. Five hundred and forty publications in English language were retrieved and categorized into five different groups. The publications were categorized as reports based on: (i) phenotypes (n = 437), (ii) mutations (n = 51), (iii) novel genes (n = 9), (iv) therapeutic interventions (n = 31), and (v) reviews (n = 12). Most of the publications were single-patient case reports describing the clinical and radiological features of the patients affected with SDs (n = 352). We enlisted all the significant Indian contributions. We have also highlighted the reports in which Indians have contributed to discovery of new genes and phenotypes. This review highlights the substantial Indian contributions to SD research, which is poised to reach even greater heights given the size and structure of our population, technological advances, and expanding national and international collaborations.